2004
DOI: 10.1093/rfs/hhi003
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Expectations in Asset Pricing Experiments

Abstract: We especially thank our discussants Thomas Langer and Marc Willinger for their helpful comments. The paper improved significantly from comments by an anonymous referee and the editor. Financial support under a NWO-Pionier grant is gratefully acknowledged

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
210
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(223 citation statements)
references
References 37 publications
11
210
1
1
Order By: Relevance
“…In recent learning to forecast experiments, described at length in Hommes et al (23), qualitatively different aggregate outcomes have been observed in the same experimental setting.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In recent learning to forecast experiments, described at length in Hommes et al (23), qualitatively different aggregate outcomes have been observed in the same experimental setting.…”
Section: Introductionmentioning
confidence: 95%
“…A number of sessions of a computerized learning to forecast experiment have been performed in the CREED laboratory at the University of Amsterdam; see (23) for a detailed description. In each session of the experiment six participants had to predict the price of an asset for 51 periods and have been rewarded according to the accuracy of their predictions.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frydman et al (2008) argues that the persistent swings in the exchange rate around long-run benchmark values are consistent with such forecasting behavior. Hommes et al (2005aHommes et al ( , 2005b develops models for a financial market populated by fundamentalists and chartists where fundamentalists use long-term expectations based on economic fundamentals and chartists are trend-followers using short-term expectations. Positive feedback prevails when the latter dominate the market.…”
Section: Introductionmentioning
confidence: 99%
“…Note that there is significant empirical evidence supporting the view that agents are boundedly rational and display rule-governed behaviour. 5 Moreover, laboratory experiments by Hommes et al (2005b) and Heemeijer et al (2009) indicate that agents tend to use simple linear forecasting rules to form predictions. In particular, agents seem to use both extrapolative and regressive expectation formation rules.…”
Section: The Modelmentioning
confidence: 99%